SERUM ELECTROLYTE LEVELS IN HEART FAILURE PATIENTS WITH A HYPERTENSION HISTORY - Suharno Usman; Christha Zenithy Tamburian; Imelda Sirait; Muhamad Nurmansyah (Faculty of Vocational Studies, Universitas Airlangga, 2025)
Background: Knowing the description of serum electrolytes in those with a history of hypertension and congestive heart failure is critical. Purpose: The purpose of this study is to look into the estimation of serum electrolytes, the correlation between serum electrolytes (sodium (Na+), potassium (K+), chlorine (Cl-)) levels with blood pressure, and the demographic characteristics of heart failure patients with a history of hypertension. Method: A retrospective design was used in this study, which used progress records (e.g., participant demographic data, medical history, and clinical laboratory tests such as serum electrolytes and blood chemistry) from patients with hypertension and Heart Failure (HF) who were hospitalized. Result: The present study established no correlation between serum electrolyte levels and blood pressure. The highest of Na+ levels were 169 mEq/L, K+ 6.4 mEq/L, and Cl- 119 mEq/L. Most participants had the habit of not smoking (87 people, 79.8%) and not consuming alcohol (91 people, 83.5%). Demographic characteristics such as gender, smoking habits, and alcohol consumption had no significant impact on serum electrolyte levels, except for a history of alcohol consumption on sodium levels, which had a significant effect (p-value = 0.014). Furthermore, an absence of correlation was observed between demographic factors and blood pressure. Conclusion: A lack of relationship between serum electrolyte levels and blood pressure. Similarly, demographic characteristics were not correlated with blood pressure. HF patients with a history of hypertension show normal serum electrolyte levels, but a significant relationship between alcohol consumption habits and sodium levels was found.